Conceptualization of Gastronomic Tourism as Innovative Tourist Model in Russia - DRACHEVA, Elena L.; SAVINKINA, Larisa A.; KULGACHEV, Ivan P.; KOSOLAPOV, Alexander B.; MELTSOV, Alexey V. (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.v12.3(51).22, 2021)
Today in Russia gastronomic tourism has made a spurt of dynamic development. This was caused not only by the current situation with COVID-2019, which contributes to the development of domestic tourism, but also by the increased interest in this type of tourism in general. Gastronomic tourism not only contributes to the growth of the flow of tourists to a particular region, in order to visit gastronomic festivals, fairs, etc. events, acquaintance with the gastronomic features of the destination, but also contributes to the development of agriculture, processing industries, and ultimately plays an important role in shaping the image of a particular region and the country as a whole. In some areas of gastronomic tourism, Russia is an innovator, whose experience can be used by other countries as well.